The VC-1 and H.264 Video Compression Standards for Broadband Video Services - Lee, Jae-Beom.; Kalva, Hari.; SpringerLink (Online service) (Boston, MA : Springer US, 2008)
The MPEG committee standardized the MPEG AVC (H.264) video coding standard in May 2003. The standard has since seen strong interest and adoption from the industry. A competing standard developed by Microsoft, referred to as VC-1, was standardized in SMPTE in April 2006. VC-1 is essentially a standardized version of Microsoft's Windows Media Video (WMV-9). Both H.264 and VC-1 are highly efficient compression standards that enable high-quality video services such as IPTV and Blu-ray Disc. H.264 and VC-1 are both mandated for high definition video services on Blu-ray Disc. These two standards are expected to form the basis for a new generation of high-quality broadband video services. The VC-1 and H.264 Video Compression Standards for Broadband Video Services covers these video coding standards, as well as issues in broadband video delivery. No other book about H.264 or VC-1 covers the standards in such detail. This book interprets the complex standards specifications and makes these new technologies accessible. Both authors have more than 12 years experience working on video compression and communications. The VC-1 and H.264 Video Compression Standards for Broadband Video Services is designed for researchers and a professional audience, including video engineers, and practitioners in consumer electronics, telecommunications and media compression industries. This book is also suitable as a secondary text or reference for advanced-level students in computer science and electrical engineering. .
Preface -- Acknowledgements -- Multimedia Systems -- Overview of MPEG-2 Systems -- Video Codec Internal and Data Flow -- Independent Slice Decoder -- Syntax Hierarchies and Encapsulation -- VC-1 Syntax Hierarchy in Bitstreams -- VC-1 Encapsulation in MPEG-2 Systems -- H.264 Syntax Hierarchy in Bitstreams -- H.264 Encapsulation in MPEG-2 Systems -- Comparisons between VC-1 and H.264 -- HRD Models and Rate Control -- Video Buffer Verifier (VBV) Model -- HRD Model in VC-1 Video -- HRD Model in H.264 Video -- Constant Delay CBR HRD Mirroring in Encoder Buffer -- Rate Control Algorithms in Standard Test Models -- Bandwidth Panic Mode in VC-1 -- Transform and Quantization -- Transform Coding -- VC-1 Transform and Quantization -- H.264 Transform and Quantization -- Intra Prediction -- Effect of Intra Prediction -- VC-1 Intra Prediction -- H.264 Intra Prediction -- Inter Prediction -- Inter Prediction -- VC-1 Inter Prediction -- H.264 Inter Prediction -- In-Loop and Out-Loop Filters -- Deblocking Process -- VC-1 In-Loop Filtering -- H.264 In-Loop Deblocking Filtering -- Out-Loop Filtering -- Interlace Handling -- MPEG-2 Interlace Handling -- VC-1 Interlace Handling -- H.264 Interlace Handling -- Syntax and Parsing -- Table-based and Computation-Based Codes -- Codes in MPEG-2 -- Codes in VC-1 -- Codes in H.264 -- References -- Index. .
Keywords: Engineering; Computer communication systems; Multimedia information systems; Computer graphics; Electrical engineering; Engineering; Communications Engineering, Networks; Multimedia Information Systems; Computer Imaging, Vision, Pattern Recognition and Graphics; Computer Communication Networks; Information Systems Applications (incl. Internet).; Electronic books